Avian Flavivirus Infection of Monocytes/Macrophages by Extensive Subversion of Host Antiviral Innate Immune Responses - Ma, Yong (J Virol, 2019)
Avian Tembusu virus (TMUV) is a newly emerging avian pathogenic flavivirus in China and Southeast Asia with features of rapid spread, an expanding host range, and cross-species transmission. The mechanisms of its infection and pathogenesis remain largely unclear. Here, we investigated the tropism of this arbovirus in peripheral blood mononuclear cells of specific-pathogen-free (SPF) ducks and SPF chickens and identified monocytes/macrophages as the key targets of TMUV infection. In vivo studies in SPF ducks and SPF chickens with monocyte/macrophage clearance demonstrated that the infection of monocytes/macrophages was crucial for viral replication, transmission, and pathogenesis. Further genome-wide transcriptome analyses of TMUV-infected chicken macrophages revealed that host antiviral innate immune barriers were the major targets of TMUV in macrophages. Despite the activation of major pattern recognition receptor signaling, the inductions of alpha interferon (IFN-α) and IFN-β were blocked by TMUV infection on transcription and translation levels, respectively. Meanwhile, TMUV inhibited host redox responses by repressing the transcription of genes encoding NADPH oxidase subunits and promoting Nrf2-mediated antioxidant responses. The recovery of either of the above-mentioned innate immune barriers was sufficient to suppress TMUV infection. Collectively, we identify an essential step of TMUV infection and reveal extensive subversion of host antiviral innate immune responses. IMPORTANCE Mosquito-borne flaviviruses include a group of pathogenic viruses that cause serious diseases in humans and animals, including dengue, West Nile, and Japanese encephalitis viruses. These flaviviruses are zoonotic and use animals, including birds, as amplifying and reservoir hosts. Avian Tembusu virus (TMUV) is an emerging mosquito-borne flavivirus that is pathogenic for many avian species and can infect cells derived from mammals and humans in vitro. Although not currently pathogenic for primates, the infection of duck industry workers and the potential risk of TMUV infection in immunocompromised individuals have been highlighted. Thus, the prevention of TMUV in flocks is important for both avian and mammalian health. Our study reveals the escape of TMUV from the first line of the host defense system in the arthropod-borne transmission route of arboviruses, possibly helping to extend our understanding of flavivirus infection in birds and refine the design of anti-TMUV therapeutics.